Two‐year experience with mycophenolate mofetil in patients with scleroderma lung disease: a case series. (26th May 2014) - Yilmaz, Neslihan; Can, Meryem; Kocakaya, Derya; Karakurt, Sait; Yavuz, Sule
Abstract To assess the effect of mycophenolate mofetil (MMF) on pulmonary functions in patients with systemic sclerosis‐associated lung disease (SSc‐ILD) who experienced an inadequate response to first line cyclophosphamide (CYC) therapy. Twelve consecutive SSc‐ILD patients who received MMF due to inadequate response to CYC as a first line agent, were retrospectively reviewed. Over the course of 2 years, pulmonary function tests (PFT) and high‐resolution computed tomography (HRCT) scans were performed. Following initial baseline tests, PFTs were continued at a frequency of every 6 months and HRCT scans were performed every 12 months. After MMF treatment, values of forced vital capacity (FVC) and diffusing capacity for carbon monoxide (DLCO) improved in three (25%) and two (16.6%) patients, respectively. It is also noted that the evaluation of serial HCRT scans showed no change in 54.5% of patients. Our case series suggested that PFT and imaging scores seemed to be stabilized by MMF in SSc‐ILD patients who were inadequate responders to CYC.